Phylogenetic affinities of the sequestrate genus Rhodactina (Boletaceae), with a new species, R. rostratispora from Thailand - Santhiti Vadthanarat (2018)
Copyright © 2018 Santhiti Vadthanarat et al. Rhodactina is a small sequestrate genus in Boletaceae with two described species, R. himalayensis and R. incarnata. Phylogenetic analyses of a three-gene dataset including atp6, tef1 and rpb2 of Rhodactina species along with selected Boletaceae species showed that all Rhodactina species formed a monophyletic clade, sister to the genera Spongiforma and Borofutus in subfamily Leccinoideae with high support. All of the taxa in the clade have a similar chemical reaction in which basidiospores turn purplish, purplish red to violet or violet grey when in contact with potassium hydroxide. The molecular analyses also showed that all Rhodactina specimens collected from Ubon Ratchathani province, northeastern Thailand, belong to a new species. Morphologically, the new species is different from others by having a markedly prominent hilar appendage and a terminal hilum on its basidiospores. Thus, the new species, Rhodactina rostratispora, is introduced with detailed macroscopic and microscopic descriptions and illustrations.